CHARACTERISTICS OF ANJASMORO SOYBEAN TEMPEH WITH DIFFERENT BOILING DURATION AND PACKAGING TYPES - Arby Surya Laksono; Marniza Marniza; Yessy Rosalina (Jurnal Agroindustri, 2019)
This study aims to determine the effect of boiling duration variations and  packaging types on physicochemical and organoleptic characteristics of Anjasmoro soybean tempeh. This study used a Completely Randomized Design with two factors, namely the factor of the initial boiling duration of soybeans (20, 30 and 40 minutes) and packaging types (PP plastic and kepok banana leaves). The results showed the interaction of two treatment variations were not significantly different at the level of 5% on physicochemical characteristics (water content and protein), but significantly different levels of Anjasmoro soybean tempeh. In general, the physicochemical characteristics of tempe have fulfilled the quality requirements of soybean tempeh (SNI 3144: 2015). Based on the results of organoleptic testing of tempeh, the interaction of two treatment variations was significantly different at the 5% level of the organoleptic characteristics of the color, aroma, and characteristics of overall fresh Anjasmoro soybean tempeh, but not significantly different in texture attributes. Whereas in the fried tempeh showed results that were not significantly different in organoleptic parameters of color, aroma, texture and overall, but it is significantly different from the taste attribute.